Recurrence mechanisms of non-muscle-invasive bladder cancer - a clinical perspective - Teoh, Jeremy Yuen-Chun; Kamat, Ashish M; Black, Peter C; Grivas, Petros; Shariat, Shahrokh F; Babjuk, Marek (Nature reviews. Urology, 2022)
Non-muscle-invasive bladder cancer (NMIBC) is an early-stage cancer without invasion into the detrusor muscle layer. Transurethral resection of bladder tumour (TURBT) is a diagnostic and potentially curative procedure for NMIBC, but has some limitations, including difficulties in ascertaining complete tumour removal upon piecemeal resection and the possibility of tumour re-implantation after the procedure. The oncological control of NMIBC is far from satisfactory, with a 1-year recurrence rate of 15-61%, and a 5-year recurrence rate of 31-78%. Various recurrence mechanisms have been described for NMIBC, such as undetected tumours upon cystoscopy, incomplete resection during TURBT, tumour re-implantation after TURBT, drop metastasis from upper tract urothelial carcinoma and field change cancerization. Understanding the recurrence mechanisms from a clinical perspective has strong implications for the optimization of NMIBC oncological outcomes, as a cure for patients with NMIBC can only be achieved by tackling all possible recurrence mechanisms in a comprehensive manner.
Keywords: nádory močového měchýře; Cystectomy; Neoplasm Invasiveness; Neoplasm Recurrence, Local; Male; cystektomie; Urinary Bladder Neoplasms; lidé; Female; mužské pohlaví; ženské pohlaví; lokální recidiva nádoru; Humans; karcinom z přechodných buněk; Carcinoma, Transitional Cell; invazivní růst nádoru